On‐Demand Selection of the Reaction Path from Imino Diels–Alder to Ene‐Type Cyclization: Synthesis of Epiminopyrimido[4, 5‐b]azepines. Issue 3 (19th November 2013) - Zhang, Yuewei; Zhu, Yue; Zheng, Lianyou; Zhuo, Lian‐Gang; Yang, Fengzhi; Dang, Qun; Yu, Zhi‐Xiang; Bai, Xu
Abstract: Controlling the mode of reaction of a reactive intermediate such as an imine or iminium ion should enable the on‐demand selection of the final products from the same starting materials. The successful execution of such a strategy will reduce the time required to prepare diverse scaffolds. The imines derived from 4‐(allylamino)pyrimidine‐5‐carbaldehydes and anilines undergo Diels–Alder reactions to give pyrimido[4, 5‐ h ][1, 6]naphthyridines in high yields. A complete switch from the intramolecular aza‐Diels–Alder (IADA) path to an ene‐type cyclization reaction was achieved by simply adjusting the reaction conditions (amount of acid catalyst, solvent, and temperature). This newly introduced ene‐type cyclization reaction was used to prepare a series of epiminopyrimido[4, 5‐ b ]azepines. To gain insight into the mechanism of the two reaction pathways, a DFT study was carried out. Theoretical calculations showed that under acidic conditions an iminium intermediate favors the low‐energy IADA pathway, which proceeds in a [4 + + 2] fashion. When acid is absent, the neutral imine intermediate favors the thermal ene‐type cyclization reaction, which takes place by transfer of an allylic proton from the allylic amine to imine, followed by a barrierless nucleophilic addition process between the in‐situ‐generated anionic allylic amine and iminium ion. Amine addition to the alkene finally gives the epiminopyrimido[4, 5‐ b ]azepines. Abstract : A complete switch from an intramolecular aza‐Diels–Alder (IADA) reaction to an ene‐type cyclization was achieved simply by adjusting the reaction conditions. A DFT study was carried out to gain insight into the mechanisms of the two reaction pathways. A series of epiminopyrimido[4, 5‐ b ]azepines were prepared using this newly introduced ene‐type cyclization reaction.